Perlindungan Hukum Terhadap Pekerja Atas Alat Pelindung Diri - Fitri Hardianti Solicha; Asri Wijayanti (Wijayakusuma Law Review, 2020)
Every worker must get a guarantee for occupational safety and health while carrying out the work relationship.This research aimed to find out the form of legal protection for workers for their personal protection devices andlegal remedies. This research was a normative juridical with statute approach. The first research result showedthat every worker was guaranteed their right to occupational safety and health integrated with the company'smanagement system. Employers were required to provide explanations and self-protective equipment to workerswho were obliged to use them. There was a threat of criminal sanctions for violating entrepreneurs. The secondresearch result showed a civil law effort. It can be done by workers if they do not get an explanation and personalprotective equipment that can conduct bipartite deliberation or mediation and continue to the PHI for the harmcaused. Criminal legal remedies can be undertaken by workers by reporting K3 violations to local labor inspectoremployees. It was concluded that the employer had the obligation to provide an explanation and self-protectiveequipment. The workers were entitled and obliged to use self-protective equipment. There were criminalsanctions for employers who violated but there were not criminal sanctions for workers who violate. Theresulting recommendations were the sanctions for workers.